2022
DOI: 10.5194/hess-26-551-2022
|View full text |Cite
|
Sign up to set email alerts
|

Improved understanding of regional groundwater drought development through time series modelling: the 2018–2019 drought in the Netherlands

Abstract: Abstract. The 2018–2019 drought in north-western and central Europe caused severe damage to a wide range of sectors. It also emphasised the fact that, even in countries with temperate climates, adaptations are needed to cope with increasing future drought frequencies. A crucial component of drought management strategies is to monitor the status of groundwater resources. However, providing up-to-date assessments of regional groundwater drought development remains challenging due to the limited availability of h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 45 publications
(95 reference statements)
1
12
0
2
Order By: Relevance
“…Compared to these episodes, the drought of 2018 in the study area was generally more extreme in terms of the duration and severity of precipitation, soil moisture, and river flow deficits, which is in line with findings for northern Europe and Switzerland (respectively Bakke et al, 2020;Brunner et al, 2019). Our study further revealed a multi-year nature of the drought of 2018 that made the event more impactful, which is in line with drought impacts that were reported in the media for Germany over this prolonged period (De Brito et al, 2020) and findings for the groundwater drought in the Netherlands (Brakkee et al, 2022). Hydrological droughts for part of the catchments and wells persisted far into 2019.…”
Section: Typical Droughts and Their Hazard And Impact Characteristicssupporting
confidence: 91%
“…Compared to these episodes, the drought of 2018 in the study area was generally more extreme in terms of the duration and severity of precipitation, soil moisture, and river flow deficits, which is in line with findings for northern Europe and Switzerland (respectively Bakke et al, 2020;Brunner et al, 2019). Our study further revealed a multi-year nature of the drought of 2018 that made the event more impactful, which is in line with drought impacts that were reported in the media for Germany over this prolonged period (De Brito et al, 2020) and findings for the groundwater drought in the Netherlands (Brakkee et al, 2022). Hydrological droughts for part of the catchments and wells persisted far into 2019.…”
Section: Typical Droughts and Their Hazard And Impact Characteristicssupporting
confidence: 91%
“…During the validation period, the model overestimates the head in the summer months. These summers were particularly dry (e.g., Brakkee et al, 2022), and possibly stresses not included in the model (e.g., pumping for irrigation) could explain these deviations, but this has not been investigated here.…”
Section: Example Results At One Observation Wellmentioning
confidence: 98%
“…Dry summers and the growing demand for freshwater increases the pressure on limited groundwater resources. The groundwater table may drop significantly during and after dry summers (e.g., Brakkee et al, 2022) due to a set of stresses on the system including a decrease in precipitation, an increase in evaporation and transpiration, lower surface water levels, and higher groundwater use for both drinking water and irrigation (e.g., Van Loon et al, 2016). The effect of pumping wells on the head is one of the few stresses on the system that can be controlled.…”
Section: Introductionmentioning
confidence: 99%
“…The models developed in this study were primarily used to improve the understanding of the groundwater systems in Switzerland. In future studies, the models can be used for other purposes as well, for example for the hindcasting of heads to study long-term groundwater drought developments (e.g., Brakkee et al, 2022), or the short-term forecasting of heads (e.g., Mackay et al, 2014). Apart from practical applications, more work is required to further improve the application and robustness of the presented workflow, although high accuracy in the modeled groundwater dynamics was already obtained.…”
Section: Discussionmentioning
confidence: 99%